Eksistensi Kekuatan Eksekutorial Bagi Kreditur Pemegang Sertifikat Jaminan Fidusia Dalam Perspektif Kepastian Hukum Di Indonesia - Herdiansyah Herdiansyah; M Khodadan Ryan Keano; Novia Sartika (Universitas Batanghari Jambi, 2026)
Fiduciary security constitutes one of the proprietary security institutions that plays an important role in supporting financing activities in Indonesia. Under Law Number 42 of 1999 concerning Fiduciary Security, a Fiduciary Security Certificate possesses executorial title having the same legal force as a final and binding court judgment. However, Constitutional Court Decision Number 18/PUU-XVII/2019 and Constitutional Court Decision Number 2/PUU-XIX/2021 have significantly altered the execution mechanism of fiduciary collateral objects. This study aims to analyze the existence of executorial power held by creditors possessing Fiduciary Security Certificates following the Constitutional Court decisions and to examine their implications for legal certainty in Indonesia. This research employs normative legal research using statutory, conceptual, and case approaches. The results indicate that although the executorial title of Fiduciary Security Certificates remains legally recognized, its execution has been restricted through requirements concerning agreement on default and voluntary surrender of collateral by debtors. This condition has shifted the paradigm of fiduciary execution and affected the effectiveness of legal protection for creditors while simultaneously creating legal certainty issues within financing practices. Therefore, regulatory harmonization is required to balance the protection of creditors’ and debtors’ rights in order to realize equitable legal certainty.